(untitled) (Experimental biology, 2020)
Indigenous fish fauna has high endemism to the Balkhash watershed. Area of indigenous fish species had been drastically reduced after negative human impact. The Alakol Lake still remains bigger refuge for indigenous fishes. Therefore investigation of growing recreational impact to fish population on shallow sites was the aim of our researches. Samples were collected during 2015-2017 by international recommendations. State of the young fishes was evaluated through up their biological characteristics. Data on size and condition factor of fish babies were presented first time for many species despite long history of fishes investigations in the Alakol Lake. Diversity indexes by Simpson and Shannon were calculated to describe fish communities. Only 5 indigenous fish species like Seven rivers’ minnow Phoxinus brachyurus, spotted stone loach Triplophysa strauchii, Sewertzov’s stone loach Triplophysa sewerzowii, plain thicklip loach Triplophysa labiata, and Balkhash perch Perca schrenkii were revealed. Alien fish species were presented by 4 species like carp Cyprinus carpio, Prussian carp Carassius gibelio, topmouth gudgeon or pseudorasbora Pseudorasbora parva, and rosy bitterling Rhodeus ocellatus. Grow rate and condition factor indicated rather good living conditions for the indigenous fishes. Alien short living fish species were not neither numerous nor permanent members of the fish assemblages. The presented data allowed us to consider modern state of shallow sites of the lake as good enough for the indigenous fish reproduction. Limitation of number of visitors and 300 meters wide protected area around the investigated sites should be reasonable for long term conservation of indigenous fish fauna in the Alakol Lake. Key words: Alakol Lake, recreational, indigenous, alien, fish fauna